A new RuIIRhIII bimetallic with a single Rh–Cl bond as a supramolecular photocatalyst for proton reduction1. Issue 65 (21st August 2015) - Zhou, Rongwei; Manbeck, Gerald F.; Wimer, Dexter G.; Brewer, Karen J.
<x xml:space="preserve">Abstract</x> Photoinitiated electron collection on the RhIII center bearing only one photo-labile Rh–Cl bond resulted in an active RuRhI species for proton reduction. The results opened a new approach to designing RuIIRhIII photocatalysts.